Assessment of Prevalence and Risk Factors for Intestinal Parasitosis, Malnutrition, and Anemia among School Children in Ghindae Area, Eritrea. (30th October 2020) - Kesete, Yafet; Tesfahiwet, Huruy; Fessehaye, Ghimja; Kidane, Yohana; Tekle, Yafet; Yacob, Asmerom; Seltene, Biemnet
Abstract : Background . Research studies on determination of risk factors for intestinal parasitic infections and related malnutrition and anemia in various tropical areas are necessary for appropriate preventive resource allocation and cost effective control. This study is aimed at evaluating the prevalence and risk factors of intestinal parasitosis, malnutrition, and anemia amongst elementary and junior school students in Ghindae area, Eritrea. Method . A cross-sectional study was conducted in 6 schools around Ghindae from February to April 2018. 460 children were selected randomly for analysis and consent was taken from guardians. The pertinent sociodemographic data was collected using a pretested questionnaire, and anthropometric measurements were carried out to determine the proportion of students with malnutrition, stunting, and thinness. Fecal samples were examined by formal-ether concentration technique, and blood specimen was collected and analyzed for the assessment of hemoglobin using Hemocue analyzers. The association between predictors and outcome variables were measured with a stepwise logistic regression model. Result . The overall prevalence of intestinal parasitosis was 45.3%. Protozoan infections (38.2%) were more prevalent than soil-transmitted helminthic infections (10.4%). The presence of different intestinal parasitic infections had statistically significant association with the residence area, hand washing habits, source of drinking water, and type of latrine used. The prevalence of malnutrition was 36.9% with 18.5% stunting and 21.2% thinness. Students of rural areas had 2.03 times more odds of having malnutrition. The current prevalence of anemia was 12.4%, out of which 7.6% had mild anemia while 4.4% of them had moderate anemia and 0.4% were severely anemic. Conclusion . The prevalence of parasitic infection among school-age children in Ghindae area was high. Unsafe drinking water sources from streams and springs were among the core problems for increased prevalence along with decreased awareness on personal hygienic and sanitation practices. Undernutrition was widely prevalent among students in Ghindae area. Height for age and BMI for age scores of all participants were found to be below the WHO growth standards. Malnutrition was in higher prevalence in rural areas outside Ghindae, which is attributed to two times higher odds than their counterparts. The magnitude of anemia found in this study is considered a mild public health problem.